2011
DOI: 10.1016/j.yebeh.2011.04.061
|View full text |Cite
|
Sign up to set email alerts
|

The role of sleep in forgetting in temporal lobe epilepsy: A pilot study

Abstract: The purpose of this study is to examine how sleep impacts memory function in temporal lobe epilepsy (TLE). TLE patients (n=7) and control subjects (n=9) underwent training and overnight testing on (1) a motor sequence task (MST) known to undergo sleep-dependent enhancement in healthy subjects, and (2) the selective reminding test (SRT), a verbal memory task on which TLE patients have shown impaired performance 24 hours after training. Sleep data was collected by polysomnography. Results indicate that TLE patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 20 publications
3
25
0
Order By: Relevance
“…These results are in line with a pilot study in temporal lobe epilepsy (Deak et al., 2011) in which patients forgot significantly more than controls over a day of wakefulness but not over a night of sleep. This pilot study did not fully control for potential group differences in learning and circadian fluctuations in performance, and the task was not sensitive to the benefit of sleep for memory consolidation in healthy control subjects.…”
Section: Discussionsupporting
confidence: 92%
“…These results are in line with a pilot study in temporal lobe epilepsy (Deak et al., 2011) in which patients forgot significantly more than controls over a day of wakefulness but not over a night of sleep. This pilot study did not fully control for potential group differences in learning and circadian fluctuations in performance, and the task was not sensitive to the benefit of sleep for memory consolidation in healthy control subjects.…”
Section: Discussionsupporting
confidence: 92%
“…The authors reported the occurrence of ALF over a period of 12 hours of wakefulness, but not over a comparable period of sleep, suggesting that ALF is not caused by disruption of sleepdependent memory consolidation. These results are in line with other findings in temporal lobe epilepsy [38,49,50]. However, some patients exhibit ALF over hours [26,27], while others over days, weeks or months [9,16,22,28].…”
Section: Accelerated Rate Of Forgettingsupporting
confidence: 92%
“…This is in line with an earlier pilot study of forgetting in epilepsy [111] and further supported by animal studies, as rat models of TLE show normal replay of behavior-driven sequences of single cell hippocampal activity during sleep [112]. In contrast, these three studies suggest that activity during periods of wakefulness following learning, possibly within the first few hours [113], may be more closely linked to ALF, as would be predicted by interference-based models of amnesia (e.g., [114,115]).…”
Section: Possible Mechanisms For Alfsupporting
confidence: 92%